Effectiveness of conservation interventions for Australian woodland birds: A systematic review. (June 2023) - Walsh, Jessica C.; Gibson, Michelle R.; Simmonds, Jeremy S.; Mayfield, Helen J.; Bracey, Clare; Melton, Courtney B.; Reside, April E.; Maron, Martine
Abstract: Summarising the evidence about 'what works' for conservation is an important first step towards implementing evidence-based practice. Australian woodland birds form diverse sets of ecological communities of conservation concern, yet despite decades of research and management, it is unclear which interventions are reliably effective. Using a systematic map and review, we synthesised the scientific evidence (142 published and unpublished studies) about the response of Australian woodland birds to 26 conservation interventions. The interventions most frequently studied were replanting, grazing management, fire management and natural regeneration. There were 106 articles that measured species richness and/or abundance. Due to the lack of a business-as-usual control or ineligible statistical reporting, only 35 % of these ( n = 37) had suitable data that we could use to synthesise the outcomes. For most interventions, there were too few comparable studies to support meta-analysis. We identified that replanting native vegetation and retaining coarse woody debris were consistently reported to have positive effects on woodland bird species richness and total abundance, albeit based on a very small sample of studies ( n = 2–3). In contrast, prescribed burning, noisy miner ( Manorina melanocephala ) control, natural regeneration, grazing management and site protection had mixed results – i.e., some studies found no effect, while others reported positive or negative outcomes. This review provides a comprehensive database of studies testing management effectiveness for Australian woodland birds, but reveals knowledge gaps in the evidence for even widely implemented interventions. We highlight the need for statistically and experimentally robust studies evaluating the effectiveness of conservation actions. Highlights: We collate evidence of effectiveness for 26 actions for Australian woodland birds. Controlling fire, noisy miners & grazing and natural regeneration had mixed results. Evidence on the effect of most interventions for richness and abundance was limited. This comprehensive database provides relevant information for decision-makers. Future studies evaluating management impact need suitable counterfactual controls.